The hidden costs of informal caregiving: a concept analysis - Jinjin Gu; Xiang Sun; Yan Shi; Shanshan Wang; Panpan Wang; Lamei Liu; Yihan Liu; Peng Wang (BMC, 2024)
Abstract Background "The hidden costs of informal caregiving" is an interdisciplinary concept. While caregivers make a significant contribution to the process of caregiving, they sacrifice their leisure time, and incur risks of dropping out of the job, impaired mental and physical health, and decreased well-being within the context of caregiving. Those invisible sacrifices are often overlooked and described as hidden costs of informal caregiving. However, the conceptualisation of hidden costs of informal caregiving has not yet been clarified and scientifically assessed. The research aimed to clarify the concept of hidden costs of informal caregiving and develop an operational definition. Methods Walker and Avant's concept analysis was conducted. Databases of CBM, CNKI, WanFang, VIP, PubMed, Embase, CINAHL, Web of Science, MEDLINE, Cochrane Library, Econlit, CINAHL and ProQuest were searched with the term "hidden costs of informal caregiving". Information about the uses of the concept, defining attributes, model cases, antecedents, consequences and empirical referents of hidden costs of informal caregiving was extracted and synthesized. Results A total of 25 articles were included. The six defining attributes of hidden costs of informal caregiving were identified as including "undertaken by informal caregivers", "the time costs of caregiving", "costs of career development" "physical well-being costs", "mental well-being costs" and "social relationship costs". Personal characteristics of the caregivers and care recipients, along with caregiving attributes, were among the antecedents. The consequences of hidden costs of informal caregiving resulted in negative influences which included poor quality of life, life-altering decisions, options for the type of care, some degree of economic hardship, decreased compliance with treatment plans and monetary value informal caregivers are willing to pay to be replaced. Conclusion This concept analysis decisively illuminated the hitherto nebulous concept and expanded the contents of hidden costs of informal caregiving, which will foster a deeper appreciation of the invisible cost of caregivers. Moreover, it will provide a reference for the study of the hidden costs of informal caregiving in future, contribute to the development of assessment tools and theoretical models of hidden costs of informal caregiving, and create a basis for designing an evidence-based care program.